Chemical composition of essential oil from leaves of seeded and seedless Citrus reticulata blanco var. kinnow - Parveen, Z; Siddique, S; Ali, Z (Bangladesh Journal of Scientific and Industrial Research, 2015)
The hydro-distilled essential oil of Citrus reticulata Blanco var. kinnow was analyzed by Gas chromatography-mass spectrometry (GC-MS). Five constituents out of fifteen constituents were identified from seeded C. reticulata oil representing 74.66% of the oil. The major constituent of the oil was ?- phellandrene (62.00%). ?-pinene(6.53%), ?-myrcene(2.81%), limonene(2.81%) and caryophyllene(0.51%) were present in considerable amount. From the low seeded C. reticulata oil, six components out of seventeen compounds were identified constituting 54.74% of the oil and the main component was ?-phellandrene (37.35%). ?-pinene(2.79%), ?-pinene(3.26%), ?-myrcene(4.16%), limonene(5.77%), caryophyllene(1.41%) were present in considerable amount. DOI: http://dx.doi.org/10.3329/bjsir.v49i3.22132 Bangladesh J. Sci. Ind. Res. 49(3), 181-184, 2014